2004
DOI: 10.1530/eje.0.1500465
|View full text |Cite
|
Sign up to set email alerts
|

Remission criteria for the follow-up of patients with acromegaly

Abstract: Objective: The aim was to evaluate the validity of current remission criteria in acromegaly, a random GH level of ,2.5 mg/l, a glucose-suppressed GH level of , 1 mg/l and a normal IGF-I level. Design: In forty-one patients treated for acromegaly (23 males and 18 females, 20-69 years) and 94 healthy subjects (50 males and 44 females, 20-78 years), basal GH and IGF-I levels and nadir GH levels after 75 g oral glucose were evaluated in decade blocks; these were assayed by sensitive immunoradiometric assays. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
2
25
0
1
Order By: Relevance
“…In the consensus statement issued in 2000 (2 ), a nadir concentration of 1 g/L in the OGTT, as measured by a sensitive immunometric assay, was used to define normalization of GH secretion, but this limit has recently been criticized for being too high (15 ). Differences in basal serum GH concentrations between healthy men and women have been observed in several studies (16 -20 ), but the nadir value during the OGTT has differed in some (18,19,21 ) but not in other studies (5,20 ).…”
mentioning
confidence: 99%
“…In the consensus statement issued in 2000 (2 ), a nadir concentration of 1 g/L in the OGTT, as measured by a sensitive immunometric assay, was used to define normalization of GH secretion, but this limit has recently been criticized for being too high (15 ). Differences in basal serum GH concentrations between healthy men and women have been observed in several studies (16 -20 ), but the nadir value during the OGTT has differed in some (18,19,21 ) but not in other studies (5,20 ).…”
mentioning
confidence: 99%
“…(3) reported basal GH levels > 5 µg/L in only 10% and > 10 µg/L in < 3% of 213 subjects aged 20 to 76 years, with a predominance of females (69%). These cut-off values (5 µg/L for men and 10 µg/L for women) also show high specificity when GH is measured with other currently available assays (3,(6)(7)(8)(9). It is important to note that the specificity of basal GH measurement using the cut-off values cited above is as high as the specificity of nadir GH in the OGTT considering the currently proposed cut-off of 0.4 µg/L (3,4,6).…”
mentioning
confidence: 77%
“…While some of them have suggested that the 1 mg/l cut-off level was satisfactory (4,5,7,13,14), others have suggested that lower cutoffs should be utilized to better define remission of acromegaly (8,9,(15)(16)(17)(18). We show here that the utility of OGTT is determined by the degree of endogenous GH hypersecretion: 100% of clinically and biochemically active acromegalic patients with 'high' GH profiles have postglucose GHn higher than 1 mg/l, while over 50% of the active 'low' GH acromegalic patients have ostensibly normal GH suppressibility by the same criterion.…”
Section: Discussionmentioning
confidence: 99%